Optimal online charging of plug-in electric vehicles considering voltage unbalance factor - Jabalameli, N.; Masoum, Mohammad Sherkat; Deilami, Sara (2018)
© 2017 IEEE. The worldwide application and grid-to-vehicle charging of plug-in electric vehicles (PEVs) are expected to tremendously grow within the next few years. Uncoordinated PEV charging in low voltage (LV) distribution networks can lead to local grid problems such as overloading of transformers and voltage unbalances. A potential solution and key challenge for PEV integration is the smart shifting of charging activities to off-peak periods. This paper investigates the impacts of single-phase PEV charging at residential houses on the three-phase distribution network. It proposes online coordinated PEV charging using a genetic algorithm (GA) to minimize the overall voltage unbalance factor (VUF) by controlling the time of charging considering voltage constraints. The impacts of uncoordinated and GA coordinated PEV charging on VUF and voltage profiles will be simulated for a real Western Australian distribution network in the Perth solar city.